A Study On Women Entrepreneurs Running Small Enterprises In And Around Chandigarh - Upadhyay, Archan (Gyan Management Journal, 2020)
Entrepreneurship is the only key that provides more job providers than seekers. The role of this concept is manifold in the increased economic activity within the country. Women entrepreneurs are leading their way to success but have to pass various hurdles in their path to success. This study was conducted on fifty women entrepreneurs through Judgemental sampling in Tricity. The enterprises selected for study wereHandicrafts, Designer clothes, Bakery Business, Organic Dairy Business, Chocolate Business, Designer Jewellery Business boutiques etc. Female Entrepreneurs faced financial problems, problems in managing personal and work life etc. The study suggests that the problems can be solved if the budding female entrepreneurs get support from all fronts be it societal, professional, government and family.